2016
DOI: 10.1186/s12891-016-1147-z
|View full text |Cite
|
Sign up to set email alerts
|

Case report - calcification of the medial collateral ligament of the knee with simultaneous calcifying tendinitis of the rotator cuff

Abstract: BackgroundCalcification of the medial collateral ligament (MCL) of the knee is a very rare disease. We report on a case of a patient with a calcifying lesion within the MCL and simultaneous calcifying tendinitis of the rotator cuff in both shoulders.Case presentationCalcification of the MCL was diagnosed both via x-ray and magnetic resonance imaging (MRI) and was successfully treated surgically. Calcifying tendinitis of the rotator cuff was successfully treated applying conservative methods.ConclusionThis is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…Since the patient in this study did not have any systemic or focal knee ailment, previous knee trauma with subsequent dystrophic calcification in MCL might potentiate the patient’s suffering. According to the literature, it takes about 2–6 weeks to develop post-traumatic calcific deposit ( 12 ); however, in the present study, the patient reported two months after the incident.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Since the patient in this study did not have any systemic or focal knee ailment, previous knee trauma with subsequent dystrophic calcification in MCL might potentiate the patient’s suffering. According to the literature, it takes about 2–6 weeks to develop post-traumatic calcific deposit ( 12 ); however, in the present study, the patient reported two months after the incident.…”
Section: Discussioncontrasting
confidence: 60%
“…A focal area of tenderness near the knee, just proximal to the joint line, is also included in the fibromyalgia classification criteria ( 10 ). In Pellegrini Stieda syndrome ( 9 , 12 ), patients usually complain of distal medial thigh pain. Knee joint pain, due to avulsion fracture of medial femoral condyle at the insertion of proximal portion of medial collateral ligament, is another differential diagnosis of medial knee pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations